The Fulfillment of Children's Maintenance Rights in Post-Divorce Families: A Case Study of Dekatagung Village - Zulaikhatun Naziha; Abdul Wahid; Abdul Halim (Walidem Institute and Publishing, 2026)
Objective: This study aims to analyze the implementation of children's maintenance rights in post-divorce families and identify the factors influencing the fulfillment of these rights in Dekatagung Village, Sangkapura District, Gresik Regency, Indonesia. Theoretical framework: The study is grounded in the theory of parental responsibility and children's rights, which emphasizes that parents, especially fathers, remain legally and morally obligated to provide financial support for their children despite marital dissolution. Literature review: Previous studies have highlighted persistent challenges in child support enforcement, including economic hardship, weak legal compliance, and changing family structures. However, limited research has explored these issues within rural Indonesian contexts through in-depth qualitative investigation. Method: This research employed a descriptive qualitative approach using a field study design. Data were collected through in-depth interviews, observation, and documentation involving six mothers who held legal custody of their children following divorce. The data were analyzed through data reduction, data display, and conclusion drawing to identify recurring patterns and themes. Results: The findings reveal that the fulfillment of children's maintenance rights in Dekatagung Village remains largely inadequate. Only one respondent reported receiving regular child support, while the remaining five experienced irregular payments or no support at all. Several factors contribute to this situation, including the former husband's economic instability, remarriage and shifting priorities, ineffective communication between former spouses, and limited legal awareness and sense of parental responsibility. These conditions indicate a significant gap between legal obligations and actual practice. Implications: The study implies the need for stronger collaboration among families, communities, and government institutions to enhance compliance with child support obligations. Novelty: The novelty of this research lies in its empirical examination of post-divorce child maintenance practices in a rural Indonesian setting, providing contextual insights into the socio-economic and legal barriers affecting the protection of children's rights.